Nanoplasmonics - Bueno-Alejo, Carlos J. (IntechOpen, 2020)
During the last few years, nanomaterials have attracted the attention of the scientific community due to their extraordinary and unique properties. Their small size, and the distinctive features that come with it, makes these materials very attractive for use in different important fields like biomedicine, sensors, or catalysis. One of the most important properties of these materials is their interaction with light and is called surface plasmon resonance. It is a phenomenon that happens on the surface of certain nanomaterials that confers them with unique properties. This remarkable characteristic has opened a whole new field called nanoplasmonics that is acquiring more and more importance among the scientific community. This book aims to review the state of the art in this new field and provide the reader with a wide overview of the new nanomaterials available and their current and future applications.